Analytical solution of telegraph equations by variational iteration method - Aisha Awais (Annals of Mathematical Modeling, 2020)
In this paper, the variational iteration method (VIM) is utilized for the solution of telegraph equations, which emerge in the propagation of electrical signals along a broadcast line. The suggested method is progressively effective and simpler to deal with as contrast with the decomposition method. Numerical outcomes demonstrate the effectiveness and exactness of the proposed VIM.